THE EFFECT OF PRICING AND PRODUCT QUALITY ON PURCHASING DECISIONS OF GARNIER FACIAL CLEANSER - Christianingrum Christianingrum (JURNAL BISNIS STRATEGI, 2022)
This research is motivated by the phenomenon of competition in the business world in the era of intense globalization. All companies are constantly trying to reach new consumers and expand their market share. The leading skin care company, namely PT. L'Oreal Indonesia, with the Garnier brand, has the advantage of being in second place in the Face Cleansing Category from 2020-2022. Quantitative descriptive research using multiple linear regression analysis. The population is the people of Pangkalpinang city, with a sample of 100 respondents using a purposive sampling technique. Research results: 1). Pricing has a positive and significant effect on purchasing decisions, showing a count value of 3.481 > table 1.984 and a significance value of 0.001 <0.05; 2). Product quality has a positive and significant effect on purchasing decisions, with the results showing a count value of 6.878 greater than table 1.984 and a significance value of 0.000 <0.05; 3). Pricing and product quality have a positive and significant effect on purchasing decisions, and the results show the results of the Fount test 149.641 > Fable 3.09 and a significance value of 0.000 <0.05